Open Government Data, Legal Obligations, and Administrative Capacity: Bridging the Gap Between Policy and Practice - Umi Umairah Suhardi; Nurhaerani Tenriwaru; Mar’atun Fitriah; Nurfadilah Nasiruddin (Magister Ilmu Pemerintahan FISIP Universitas Mulawaraman, 2026)
Data on open government (OGD) implementation in Indonesia remains under-researched, particularly in provinces outside Java. While existing OGD studies have examined the legal framework or technical administrative dimensions separately, no studies have simultaneously integrated legal obligations, administrative capacity, and political commitment as determinants of OGD outcomes. This study addresses this gap by investigating OGD policy implementation in six districts in West Sulawesi Province, one of the youngest and most administratively challenged provinces in Indonesia, through a qualitative case study design with 12 purposively selected key informants, field observations, and document analysis covering the period 2021–2025. The results show that OGD compliance scores across all West Sulawesi districts increased from 33.2% in 2021 to a projected 57.0% in 2025, but remain below the national threshold of 60%. Theoretically, this study contributes to OGD implementation theory by demonstrating that in low-capacity local governments, administrative capacity is a constraint that determines whether legal obligations and political commitments translate into substantive outcomes, thereby extending the application of the implementation capacity framework to the context of subnational digital governance. Practically, this study recommends a sequential, capacity-focused reform agenda, prioritizing digital skills training, infrastructure investment, and organizational culture transformation as prerequisites for effective OGD governance in Indonesia's periphery.